The Role of Culture on Islamic Architecture - Azhari Ebeid Abu elreish; Eka Cahya Prima (Perhimpunan Intelektual Muslim Indonesia, 2021)
Islamic architecture is an ongoing argument for an extended period. Is it Islamic architecture, Muslim architecture, or architecture in Islam? Is it just visual elements or a way to use the inner space? Whatever the answer is, we will use the term Islamic architecture in this paper. To search and dig out the identities of so-called Islamics. This paper is seeking after these identities and their relations with Islamic culture to solve international architecture concepts without modifications or adaptation. The main goal is to extract the sociocultural aspects that define that architecture to be called Islamic Architecture. An analytical research method uses some attempts to interact the environmental conditions and social aspects with cultural and religious values to define Islamic architecture's identity. The study result and summary could be used to evaluate the satisfaction of the built environment of Muslims when and wherever they are. As a comprehensive result, Islamic Design Principles, Islamic Planning Principles, and Islamic Urban Design Principles could be extracted from Islamic sources and used everywhere at any time by anybody. These design principles may be used to upgrade the workability of the existing residential buildings simply by revising the opening's location, heights, and treatments. Architecture with that dynamic, flexible culture gives its identity a chance to compete globally to survive locally.